Effect of Cloud occurrences on Tropospheric and Stratospheric Ozone over Alipore (22.52oN, 88.33oE) and Bangalore (12.97°N, 77.56°E), India - Jana P. K.; Bhattacharyya S.; Ghosh S.; Das P. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The paper presents the nature of annual cycles of tropospheric and stratospheric ozone, and cloud occurrences, monthly variations of tropospheric and stratospheric ozone, and cloud occurrences, and variations of tropospheric and stratospheric ozone with occurrences of cloud for the period January, 2005 to December, 2011 Alipore (22.52oN, 88.33oE) and Bangalore (12.97°N, 77.56°E), India. Annual cycle of low- level cloud occurrences depicts that the low-level cloud over Alipore and Bangalore had been noticed to occur for many days and nights, particularly in the months from June to September. The low level cloud occurrences were found in winter months and post-monsoon period. The concentration of tropospheric ozone over Alipore had a greater value than that over Bangalore, but the concentration of stratospheric ozone over Alipore was relatively less. The effect of cloud occurrences on tropospheric and stratospheric ozone concentration over Alipore and Bangalore has been critically analyzed, explained and compared. It has been observed that the concentration of tropospheric ozone had a decreasing tendency with cloud occurrences, whereas the stratospheric ozone has a slight increasing trend with the increase of cloud occurrences and vice versa. The related possible chemical and physical explanation of role of cloud occurrences on tropospheric and stratospheric ozone has been offered.